High toughness multifunctional organic hydrogels for flexible strain and temperature sensor. Issue 40 (11th October 2021) - Chen, Hongjie; Huang, Jianren; Liu, Jiantao; Gu, Jianfeng; Zhu, Jundong; Huang, Bing; Bai, Jin; Guo, Jinquan; Yang, Xiaoxiang; Guan, Lunhui
Abstract : A wearable multifunctional sensor was proposed, consisting of strain and temperature sensors, both of which were fabricated by a rationally designed toughness and conductive organohydrogel. Abstract : The conductive hydrogel has shown extensive applications in multifunctional sensors. However, the intrinsic characteristics of conductive hydrogels, such as lacking anti-freezing, mechanical strength, and being easily dehydrated have hindered their application in wearable devices. Herein, reduced graphene oxide (rGO) and graphene oxide (GO) nanosheets were incorporated into a porous cross-linking poly(vinyl alcohol) (PVA) hydrogel network within dimethyl sulfoxide (DMSO)/H2 O binary solvent. A honeycomb-like dense micro-network and uniform dispersion conductive tough fillers endow high toughness (3.1 MPa @ 600% strain) and conductivity to the organohydrogel. With the intense interaction between water and DMSO, the organohydrogel exhibits reliable mechanical and electronic performance in a wide range of temperatures (−30 to 60 °C) and possesses excellent ambient stability. The organohydrogel had excellent sensitivity and linear repeatable response ability in both mechanical and thermal stimulation. With the integrated unique features, the sensitive organohydrogel was developed for a multifunctional sensor. As a strain/pressure sensor, it exhibited a sensitive response to the applied tensile or compressed strain with repeatability and durability. As a temperature sensor, it presented excellent linear and reliable thermal response with a high sensing accuracy. This work provides a new paradigm for designing a wearable multifunctional sensor or E-skin, which is used to detect the motion or temperature of the human in the future.